2012
DOI: 10.1021/jp3070757
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Aqueous Solution Route to Reliable p-Type Doping in ZnO with K: Growth Chemistry, Doping Mechanism, and Thermal Stability

Abstract: In this paper, we identified how the growth environment chemistry can critically influence the type and nature of the incorporated K defect in ZnO films grown using the aqueous solution route, which explains the switching between p-and ntype conductivities under different doping or thermal annealing conditions. This was achieved by relating the growth environment to the structural, optical, and electrical characteristics of the films. The thermal behavior of these defects up to 700 °C confirms the proposed dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To transform the NW growth into a more deterministic process, it is critical to identify both the dominant growth mechanisms and the effect of diffusive transport versus reaction. In particular, identifying the c -plane growth mechanism is important for controlling the NW growth rate, impurity interaction, , and dopant incorporation . Generally, solution-phase crystal growth mechanisms can be determined by observing the facet growth rate-supersaturation relationship or special surface features. ,, Applying this approach to ZnO requires constant Zn 2+ and OH – concentrations, but typical bulk synthesis, ,, where a solution containing fixed amounts of reactants is sealed and heated, is unsuitable because reactant supersaturation decreases during growth due to consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To transform the NW growth into a more deterministic process, it is critical to identify both the dominant growth mechanisms and the effect of diffusive transport versus reaction. In particular, identifying the c -plane growth mechanism is important for controlling the NW growth rate, impurity interaction, , and dopant incorporation . Generally, solution-phase crystal growth mechanisms can be determined by observing the facet growth rate-supersaturation relationship or special surface features. ,, Applying this approach to ZnO requires constant Zn 2+ and OH – concentrations, but typical bulk synthesis, ,, where a solution containing fixed amounts of reactants is sealed and heated, is unsuitable because reactant supersaturation decreases during growth due to consumption.…”
mentioning
confidence: 99%
“…Identifying the c -facet growth mechanism means that the growth rate can be controlled by changing the Zn 2+ concentration. This result also has implications for interaction of the c -facet with impurities because dopant incorporation frequently takes place at the c- facet due to its higher surface energy compared to the m -facet. , Impurity adsorption also offers the opportunity for growth control through modification of the growth rate. The variation of facet growth rate with additive concentration strongly depends on the facet growth mechanism , and so this understanding will allow further tuning of growth rates via impurity addition, which we show next.…”
mentioning
confidence: 99%
“…Tay et al have studied the K-doped ZnO grown by a low-temperature aqueous solution technique. [85] Figure 28 shows the schematic diagram of the potassium doping mechanism. They have found that in K-poor condition, the K Zn -H i is the main passivator to K Zn , while in K-rich condition, the K i and K Zn -K i complex would act as the 047702-13 acceptor-killers.…”
Section: Mono-doping Approachmentioning
confidence: 99%
“…28. (color online) Schematic diagram showing the effects of the pH and K + /Zn 2+ concentration ratios (R) on the type of K defect that is incorporated into samples A-E, as well as on the Hall effect, hole (p)and electron (n) concentrations in unit cm −3 [85].…”
mentioning
confidence: 99%